Experimental study of biopolymer in corrosion resistance for industrial exposure condition. (2021) - Beulah Gnana Ananthi, G.; Sivakumar, N.; Deepak, M.S.
Abstract: Many RCC structures have been built in the last century but these structures are in need of repair within 10–20 years of its construction. The reason for this premature distress and deterioration points towards corrosion of steel reinforcement bars used in these structures due to weakening of concrete. The enormous number of structures that needs immediate repair and renovation opens up a huge potential for research in this area. The repair work done in a conventional way using normal cement composite did not work. Whereas repair work done with scientific approach using high and technically competent materials (like epoxies) leads to uneconomical solutions and not durable to withstand our tropical climatic conditions. India being a flourished nation with infinite resources giving us a numerous number of bio-polymers that were used in ancient times in ancient construction, if these bio polymers are identified experimentally for their benefits it would give way to eco-friendly economical and long-lasting structures. The use of corrosion inhibitor is one of the most widely used countermeasures, because of their simplicity in applications and is relatively less expensive. The natural bio polymers are organic materials available from selected plants, seeds, fruit extracts. Plant extracts corrosion inhibitors are cheap, non-toxic and environmental friendly. Organic inhibitors offer protection by adsorbing and forming a protective film on the steel surface. Turmeric, Neem extracts in concrete as corrosion inhibitor in different ratio and as a combination are to be studied at depth, as they are commonly available and there is no constraint in getting these resources throughout the year. An eco-friendly, economical, Non-Toxic and user-friendly corrosion inhibitor can be given from this experimental study. The feasibility study has been made and phytochemical analysis results give positive results for a better result giving corrosion inhibitor.